Analisis Pengendalian Kualitas terhadap Produk pada CV. Zam-Zam Furniture Menggunakan Peta Kendali P. (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2022)
CV. Zam-Zam Furniture manufactures various kinds of furniture products, such as wardrobes, tables, chairs, beds, bookshelves, stacking shelves, etc. The problem faced is the emergence of defects in the product. Defective products occur due to errors in the production process, such as lack of planning, supervision and control, worker negligence, and others. The high number of defective products will increase the cost of the production process which will cause losses for the company. The purpose of this study is to identify the number of defective products and determine the causes of defective products and provide alternative repairs. To make it easier to analyze the causes of disability, the research methods used are P control charts and cause and effect diagrams (fisbone diagrams). The results showed that there were two types of damage, namely bumps and scratches, using the P control chart the final product quality control chart with the final total CL value of 2.677, UCL 4.112, LCL 1.243 with the proportion of defects of 2.677 which means the quality control process is within control limits because the value of the proportion of defects is smaller than the UCL value. The results of the analysis with cause-and-effect diagrams that show the causes of poor product quality are labor factors, methods, machines, environmental materials and tools.